Interactive communication on university websites in Ecuador - Segura-Mariño, Adriana Graciela (2020)
This research evaluates the communication that the 60 accredited universities in Ecuador develop on their websites. The objective is to determine the importance they attach to interactive communication and to analyze whether there is association with institutional factors, with the position in world rankings and with the website traffic. Content analysis was used and a Web Communication Index –WCI– was created to identify the presence of communication management and the adoption of interactive channels in the portals; the Similar Web tool was also used. Among the main results, it was found that the universities sites have low levels of traffic in their category, that the presence of communication management is minimal, and that there are statistically significant differences according to the type of financing and the year of foundation. Assessing the potential of websites is key to improving ranking position and web traffic.